DIONISIO 3.0: Comprehensive 3D nuclear fuel simulation through PCMI cohesive and PLENUM models - Goldberg, Ezequiel (2019)
We present a new version of the DIONISIO code, extending its capabilities to three-dimensional domains. Adding to the functionality that divides the rod in a user-defined number of segments, the user can now choose the dimensionality of the domain in which a representative pellet-gap-cladding system is solved. To achieve this, we have developed a new algorithm to simulate the contact between pellet and cladding based in Cohesive Finite Elements, a natural mode to approach this issue. We present our results testing this kind of contact element in order to validate the concept. Alongside the contact algorithm, we have included a model of the plenum domain in three dimensions, treated using an external FEM mesh created ad hoc. DIONISIO reads this mesh adapting it to the specific case to be simulated and solves the energy equation inside the plenum following specific boundary conditions. We compare the new models to selected experiments under irradiation, in normal or accident conditions, for validation, with results showing a high correlation with said experiments.